The Change Laboratory for Teacher Training in Entrepreneurship Education A New Skills Agenda for Europe - Morselli, Daniele (SpringerBriefs in Education, 2019)
This open access book illustrates a new type of formative intervention for in-service teacher training in entrepreneurship education. The book describes a Change Laboratory and shows how teachers and workshop assistants develop the idea of a multidisciplinary project entailing the design of a self-service and parking lot in a dismissed area close to the city centre. The multidisciplinary project is taken as example of how an idea is debated and turned into collective action and change, the very essence of initiative and entrepreneurship. The Change Laboratory thus increases the participation of students, teachers and stakeholders in the school towards a new curriculum through the implementation of a multidisciplinary project connecting school with the world outside and working life. The book features a foreword by Luke Pittaway, USASBE Entrepreneurship Educator of 2018. The manuscript discusses key concepts of Cultural Historical Activity Theory's Change Laboratory as a formative intervention in a coherent and accessible manner. Beyond that it carefully illustrates how the Change Laboratory and its principles of double stimulation and ascending from the abstract to the concrete can be used as a theory of change to address one of the difficult and new demands of the European Union's New Skills Agenda. The author takes the reader through the expansive learning journey and uses strong evidence to show how a new object can be developed, and how associated tensions and contradictions can be surfaced and tackled by actors with a partially shared object, and how a new concept can be formed and enriched through implementation and reflection in a manner that generates collective transformative agency. (Reviewer) This project has received funding from the European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie Grant Agreement No. 654101. ; Discusses a new and emerging topic in teacher training For the first time the change laboratory is used for teacher training in entrepreneurship Discusses an example of how the change laboratory can be implemented in a multidisciplinary project